9th Five Year Plan 1997-2002 Proposals Volume-II 1. Sector : Rural Development Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1997)
The main objective of Integrated Rural Energy Planning Programme is to develop, design and implement rural energy project so as to meet, the cooking and lighting energy needs of people living in rural areas / villages. This is a new component of minimum needs programme under the 20 Point Programme of G.O.I. House-holds surveys are conducted in rural area for ascertaining the availability of resources and requirements of energy and project reports for various blocks are prepared so as to provide economical mix of both the Conventional and Non-Conventional Sources of Energy for meeting the domestic energy needs.
Andaman and Nicobar Administration, Planning Department